2019
DOI: 10.1073/pnas.1904260116
|View full text |Cite
|
Sign up to set email alerts
|

Radiokrypton unveils dual moisture sources of a deep desert aquifer

Abstract: In arid regions, groundwater is a vital resource that can also provide a long-term record of the regional water cycle. However, the use of groundwater as a paleoclimate proxy has been limited by the complex hydrology and the lack of appropriate chronometers to determine the recharge time without complication. Applying 81Kr, a long-lived radioisotope tracer, we investigate the paleohydroclimate and subsurface water storage properties of the Nubian Sandstone Aquifer in the Negev Desert, Israel. Based on the spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 47 publications
(52 reference statements)
1
19
0
Order By: Relevance
“…(). Some hints for an increase in TP frequencies over the study area, which could have triggered significant hydro‐geomorphic effect do exist (Armon et al, ; Yokochi et al, ), however, the question of past frequencies of geomorphic‐efficient events in the region is still open.…”
Section: Discussionmentioning
confidence: 99%
“…(). Some hints for an increase in TP frequencies over the study area, which could have triggered significant hydro‐geomorphic effect do exist (Armon et al, ; Yokochi et al, ), however, the question of past frequencies of geomorphic‐efficient events in the region is still open.…”
Section: Discussionmentioning
confidence: 99%
“…Water locked deep in Earth's major ice sheets or stored in its aquifers is water that fell from the atmosphere as rain and snow over time and as long ago as hundreds of thousands to millions of years ago. Radioactive isotopes analysed from groundwater samples have been used to characterize the age of Earth's ground water as illustrated in the studies of Yokochi et al [8] and Gleeson et al [9]. Yokochi et al [8] used radiokrypton 81 Kr, a radioactive cosmogenic isotope, to determine the paleo-climatic sources of recharge of the subsurface water in the Nubian Sandstone Aquifer in the Negev Desert, Israel.…”
Section: Introductionmentioning
confidence: 99%
“…Radioactive isotopes analysed from groundwater samples have been used to characterize the age of Earth's ground water as illustrated in the studies of Yokochi et al [8] and Gleeson et al [9]. Yokochi et al [8] used radiokrypton 81 Kr, a radioactive cosmogenic isotope, to determine the paleo-climatic sources of recharge of the subsurface water in the Nubian Sandstone Aquifer in the Negev Desert, Israel. They could identify two distinct moisture sources of the recharge: one less than 38 ka from the Mediterranean and the other approximately 361 ka from the tropical Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…This is demonstrated by radiokrypton dating of NAS groundwater in Sinai and the Negev Desert, which distinguished two moisture sources of recharge under cooler conditions compared to the present: a recent one with elevated d-excess from the Mediterranean cyclones during the last 38 ky and an older source, 361 ± 30 ky ago, with low d-excess from the tropical Atlantic (Yokochi et al, 2019;Table S7). The recent high d-excess groundwater component was locally recharged from the Nubian sandstone outcrops in Sinai and the Negev Desert (Abouelmagd et al, 2014;Yokochi et al, 2019) S8) showed that the mean values of dexcess for Rafah and Al-Arish stations were 18‰ and 16.9‰, respectively compared to a lower mean value of Cairo station which was 7.3‰.…”
Section: Oxygen and Hydrogen Isotopic Composition (δ 18 O And δD)mentioning
confidence: 93%